2005
DOI: 10.1088/1367-2630/7/1/251
|View full text |Cite
|
Sign up to set email alerts
|

Quantum master equation descriptions of a nanomechanical resonator coupled to a single-electron transistor

Abstract: We analyse the quantum dynamics of a nanomechanical resonator coupled to a normal-state single-electron transistor (SET). Starting from a microscopic description of the system, we derive a master equation for the SET island charge and resonator which is valid in the limit of weak electro-mechanical coupling. Using this master equation we show that, apart from brief transients, the resonator always behaves like a damped harmonic oscillator with a shifted frequency and relaxes into a thermal-like steady state. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 36 publications
(122 reference statements)
0
56
0
Order By: Relevance
“…1(a)]. This system has been theoretically studied [3][4][5][6][7] and it has been experimentally shown [1,2] that lasing can be achieved. Theoretically it has also been shown that an SSET can be used to create a nonclassical photon distribution in a resonator [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…1(a)]. This system has been theoretically studied [3][4][5][6][7] and it has been experimentally shown [1,2] that lasing can be achieved. Theoretically it has also been shown that an SSET can be used to create a nonclassical photon distribution in a resonator [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This has turned out to be a highly successful approach, in particular to describe such various systems as NEMS coupled to single electron transistors (SETS) [9][10][11] , FranckCondon blockades 12 in transport through molecules with strong electron-phonon coupling, or quantum shuttles [13][14][15][16] . From the theory of electronic transport through nanostructures 17 , however, it is known that such approximations usually are reliable only in the limit of high external voltage bias, where non-Markovian effects 18 due to quantum coherences between the external reservoirs and the electronic system (SET, quantum dot etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach has already been employed in the past for describing systems such as a metallic [22] or a superconducting single electron transistor [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the following, terms stemming from the principal value are neglected since they lead to small corrections in the perturbative regime [22,40]. Denoting withρ n I,qq (t) = n, q|ρ I (t)|n, q , the GME has the compact form (here and in the following, 0 n 2 unless stated otherwise)ρ…”
mentioning
confidence: 99%